PENGOLAHAN RUMPUT LAUT Eucheuma sp. BAGI KELOMPOK MASYARAKAT DESA TABLOLONG, KUPANG BARAT, NTT - Tangguda, Sartika; Siahaan, Irandha C.M.; Hariyadi, Dimas; Valentine, Riris (Jurnal Pengabdian Perikanan Indonesia, 2022)
Seaweed is a fishery commodity that has been widely processed into consumption and non-consumption products. Tablolong Village is located in Kupang Regency which is one of the locations for Eucheuma sp. The Covid-19 pandemic has had the effect of decreasing the price of seaweed, thus affecting the income of people who work as seaweed cultivators. The repeated use of seeds also causes the quality of the seaweed to decrease which in turn lowers the selling price of the seaweed. This activity aims to increase the selling price of seaweed through processing seaweed into seaweed lunkhead and seaweed noodles for the people of Tablolong Village, West Kupang, NTT. This community service was carried out in October – December 2021 through outreach activities and training on making seaweed lunkhead and seaweed noodles located in Tablolong Village, West Kupang District, Kupang Regency, NTT. The socialization and training activities on making seaweed lunkhead and seaweed noodles were carried out on October 19, 2021. The activity began with the provision of material on seaweed and processed seaweed which was then continued with the practice of making seaweed lunkhead and seaweed noodles by women. activity participants. The participants of the activity seemed enthusiastic about participating in the activity and were able to directly make the processed seaweed products. The activity participants also innovated to make pastries with a mixture of seaweed so that they could produce delicious and nutritious snacks. Based on the results of the activity, it can be concluded that the price of seaweed can be increased again through processing seaweed into various consumption products so that it can open up new business opportunities for the Tablolong Village community.